(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Expressed emotion (EE) is an important indicator of the caregivers’ emotional attitudes and behaviors toward patients with serious mental illnesses and has been associated with treatment outcomes, relapse, and caregiver burden. Aim & Objectives: The present study aimed to assess and compare the EE among caregivers of patients with Bipolar Affective Disorder (BAD), Schizophrenia, & obsessive-compulsive disorder (OCD), and to examine its relationship with illness severity. Material & Methods: A total of 255 caregivers were enrolled and equally distributed into three groups: caregivers of patients with BAD (n=85), schizophrenia (n=85), and OCD (n=85). Expressed emotion was assessed using the Family Attitude Scale (FAS) and Family Emotional Involvement and Criticism Scale (FEICS). Illness severity was evaluated using the YMRS, HAM-D, PANSS, and Y-BOCS scales. Data were analysed using SPSS version 25, with p≤0.05 considered statistically significant. Results: Sociodemographic characteristics of the caregivers were comparable across all groups. Caregivers of BAD patients demonstrated significantly higher FAS scores (49.40±5.20), perceived criticism, emotional involvement, and total FEICS scores compared with caregivers of schizophrenia and OCD patients (p<0.001). No significant associations were found between EE and caregiver sociodemographic variables. Correlations between illness severity and EE measures were generally weak across all diagnostic groups. Conclusion: Caregivers of patients with BAD exhibited significantly higher levels of expressed emotion than caregivers of schizophrenia and OCD patients. The findings suggest that EE is influenced more by the nature of the psychiatric illness than by caregiver sociodemographic factors. Disorder-specific psychosocial interventions aimed at reducing caregiver burden and enhancing coping skills may improve both caregiver well-being and patient outcomes.